Model establishment and operation optimization of the casing PCM radiant floor heating system. (15th February 2020) - Lu, Shilei; Gao, Jingxian; Tong, Haojie; Yin, Shuai; Tang, Xiaolei; Jiang, Xiangyang
Abstract: In this study, a new two-dimensional model of CPRF was developed in TRNSYS. Its accuracy was validated by a full-scale experiment. The effects of key parameters of CPRF coupled with solar water heating system on indoor temperature was analyzed. The single factor analysis revealed that reducing tube pitch and solidification temperature, increasing PCM layer thickness and solar collector area could increase indoor temperature. The orthogonal test analysis indicated that tube pitch has the greatest impact on the average indoor temperature. The CPRF heating system coupled to solar energy and an electric boiler operating on valley electricity (CSSEBV) was proposed to ensure stable heating. It was optimized by GENOPT. The optimal parameters are that the tube pitch is 0.28 m, the PCM layer thickness is 0.02 m, the solar collector area is 12.5 m 2 and the operating time of the electric boiler is 2h. The economy, energy saving property and environmental benefits of four systems were also compared and analyzed. Highlights: A new two-dimensional model of CPRF is developed in TRNSYS. The single factor analysis and the orthogonal test analysis are used to analyze the effects of key parameters. CEI is used for system optimization. Economy, energy saving property and environmental benefits are analyzed. Can provide guidance for the design of the system components and their parameters in a CFRP heating system.